EXPLORING RISK FACTORS FOR UNCONTROLLED HYPERTENSION IN BUKITTINGGI, INDONESIA: FINDINGS FROM A CROSS-SECTIONAL STUDY: Usia, Perilaku Merokok, dan Kondisi Psikologis yang Berhubungan dengan Hipertensi Tidak Terkontrol di Bukittinggi, Indonesia - Cici Apriza Yanti; Ratna Djuwita; Evi Martha; Besral Besral; Noor Mastura Mohd Mujar; Tika Ramadanti (Universitas Airlangga, 2026)
Background: Uncontrolled hypertension remains a major public health problem and increases the risk of cardiovascular complications. Limited evidence is available regarding behavioral and psychological determinants of uncontrolled hypertension in secondary healthcare settings in Indonesia. Purpose: This study aimed to identify factors associated with uncontrolled hypertension among hypertensive patients. Methods: A cross-sectional study was conducted among hypertensive patients treated during January–December 2023. A total of 202 patients were selected from medical records using purposive sampling. Variables examined included age, smoking behavior, psychosocial stress, and anxiety status. Anxiety was identified based on standardized psychological assessments recorded in medical records. Data were analyzed using chi-square and logistic regression tests. Results: Age, smoking behavior, and anxiety were significantly associated with uncontrolled hypertension. Smoking habits (p=0.03; OR=1.55) and anxiety (p=0.001; OR=3.62) increased the likelihood of uncontrolled blood pressure. Age was also significantly associated with uncontrolled hypertension (p=0.04; OR=0.47). Conclusion: Psychological factors, particularly anxiety and smoking behavior, play an important role in hypertension control. Older patients may require closer blood pressure monitoring and regular follow-up to improve hypertension management. Integrating mental health support alongside smoking-related interventions may help improve blood pressure control in clinical settings.